A Compartmental Mathematical Model for Examining Transmission data of COVID-19 Pandemic in India - Sahoo, Chandan Kumar; Paul, Kailash Chandra; Mishra, Nilamadhba (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
IT is public knowledge that the World Health Organization declared the COVID-19 outbreak a Public Health Emergency of International Concern on 30th January 2020 and a pandemic on 11th March of the same year. Its origination was traced to Wuhan in China. Till date, it has spread to around 222 countries in the world, including India. One of the major causes of the snowballing increase in COVID-19 cases has been the scarcity of knowledge on the behavior of the new virus and the awareness regarding the basic preventive practices to be adopted by people during the preliminary days of the spread of the infection. The very 1st case in India was logged on 15th February 2020, and since then, the caseload of infected persons has snowballed to over 2.67cr only in India and 159.8 million cases worldwide, as recorded by the Worldometer. The spreading rate of COVID-19 version 2.0 has been phenomenal as compared to the version1.0. Countrywide complete and or partial lockdowns, followed by immediate isolation of infected persons, were the measures initiated by the authorities in order to contain the spread of the disease. The aim of the study is to suggest means to reduce the active cases and control the transmission risk and mortality rates. The research thus helps to calculate and predict the threshold value of the disease. In addition, the Environmental Impact Assessment Tool (EIAT) was used to perform the sensitivity analysis to determine the robustness of the assessment by examining the extent of the evolution and impacts of the pandemic in the country. The constructed control model introduced five control variables as the backbone of the adopted control strategies. The simulated results and analysis carried there upon give strong indication that quarantine and provision of timely and appropriate medical attention to the infected individuals will help reduce the number of critically infected cases to a considerably low level, which will further arrest transmission rate, mortality and active ceases in India.